Genealogisch-poststrukturalistische Ökonomiekritik und Kritik der politischen Ökonomie: Eine Aufforderung zum Tanz - Pahl, Hanno (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2012)
This article discusses pragmatic and productive encounters of post-structuralist and Marxian critiques of the economy. It is shown that to contribute to the goal of a sufficient analysis of contemporary capitalistic societies, no full conceptual integration of both bodies of theory is needed. The initial focus addresses the core-concepts of discourse and economic categories, arguing that the perspectives do not contradict each other, but point to quite similar assumptions, only at different levels of abstraction. The next section outlines two more concrete post-structuralist variants of critique, balancing them with regard to the works of Marx. The following section discusses material analyses, ending with a proposal on how to use insights and concepts of both perspectives to fine-tune our historicallyspecific understanding of capitalism.